Ultra-High-Molecular-Weight Polyethylene Rods as an Effective Design Solution for the Suspensions of a Cruiser-Class Solar Vehicle. (13th October 2019) - Minak, Giangiacomo; Brugo, Tommaso M.; Fragassa, Cristiano
Abstract : Ultra-high-molecular-weight polyethylene (UHMWPE) is a subgroup of the thermoplastic polyethylene characterized by extremely long chains and, as result, in a very tough and resistant material. Due to remarkable specific mechanical properties, its use is gradually being extended to multiple fields of application. This study describes, perhaps for the first time, how the UHMWPE can represent a valid material solution in the design and optimization of suspensions for automotive use, especially in the case of extremely lightweight vehicles, such as solar cars. In particular, in this design study, UHMWPE rods permitted to assure specific kinematic trajectories, functionalities, and overall performance in an exceptionally light suspension systems, developed for an innovative multioccupant solar vehicle. These rods reduced the weight by 88% with respect to the classic design solutions with similar functions, offering, at the same time, high stiffness and accuracy in the movements. An experimental campaign was conducted to evaluate the ratcheting behaviour and other mechanical properties needed for a proper design and use.